Cardiomyopathy in Murine Models of Systemic Sclerosis. Issue 2 (February 2015) - Venalis, Paulius; Kumánovics, Gábor; Schulze‐Koops, Hendrik; Distler, Alfiya; Dees, Clara; Zerr, Pawel; Palumbo‐Zerr, Katrin; Czirják, László; Mackevic, Zygmunt; Lundberg, Ingrid E.; Distler, Oliver; Schett, Georg; et al.
<x xml:space="preserve">Abstract</x> Objective Cardiomyopathy has emerged as a leading cause of death in patients with systemic sclerosis (SSc). However, the pathogenesis of SSc‐related cardiomyopathy is poorly understood, and new therapies as well as platforms for testing are needed. The aim of this study was to characterize the histopathologic features of cardiomyopathy in patients with SSc and in common mouse models of SSc. Methods The histopathologic features of myocardial tissue specimens obtained at autopsy from 5 subjects with SSc and 5 control subjects matched for sex, age, and cardiovascular risk factors were evaluated and compared with those of myocardial tissue specimens obtained from 3 common mouse models of SSc with systemic manifestations: Fra‐2–transgenic mice, mice with sclerodermatous chronic graft‐versus‐host disease (GVHD), and TSK‐1 mice. Results Myocardial tissue from autopsy subjects with SSc and no clinically manifest cardiac involvement showed endothelial cell apoptosis with reduced capillary density, perivascular inflammation, myofibroblast differentiation, and accumulation of collagen. Only selected features of SSc‐related cardiomyopathy were observed in the mice with chronic GVHD and TSK‐1 mice. However, the myocardial tissue of Fra‐2–transgenic mice mimicked all features of SSc‐related cardiomyopathy and also demonstrated comparable vascular, inflammatory, and fibrotic manifestations. Of note, the expression of Fra‐2 was also increased in the myocardium of autopsy subjects with SSc. Conclusion We demonstrate that all typical manifestations of SSc‐related cardiomyopathy are mimicked in Fra‐2–transgenic mice. Moreover, overexpression of Fra‐2 in the myocardium of autopsy subjects with SSc may suggest similar underlying pathogenic mechanisms. Thus, Fra‐2–transgenic mice might be a suitable preclinical model with which to study the mechanisms of and therapeutic approaches to myocardial involvement in SSc.